EFFECT OF COOKED AND GERMINATED BEAN (VICIA FABA) ON OBESITY IN RATS - Soheir Ahmed Al-Masri (Journal of Animal and Plant Sciences, 2015)
This study examined the effects of cooking and germination of faba bean on its nutrient Composition and anti obesity potential in obese rats that were fed a high fat diet to induce obesity for 4 weeks before experimental study (60 days). Rats were divided into 6 groups (8 rats each). The first group served as a control (-ve) and was fed basal diet only. Obesity was induced in the other five groups in four weeks. They were fed on basal diet with 20% tallow in replacing of starch to induce obesity. The obese rats were classified into five groups: (obese control +ve), (10% cooked faba bean), (20% cooked faba bean), (10% germinated faba bean) and (20% germinated faba bean). Chemical results showed that raw bean had higher values of fat, carbohydrate, while cooked bean showed higher minerals (calcium, sodium andiron) and vitamins content (A and E).Germinated bean had higher contents of protein, fiber, ash and Zinc. Results showed that a significant increase in all parameters (except HDLc) was obtained in obese control positive as compared to control negative group(-ve). Similarly increase in T3, T4 leptin, ALT, AST and glucose was obtained in control obese positive group as compared to control negative group. Treatment with faba beans showed positive effect on all these parameters. Lipid profile also showed positive effect of faba beans as significant decrease in all parameters except HDLc was observed in group treated with faba beans as compared to obese group. It is concluded from the above study that faba bean especially germinated faba beans have beneficial effects against obesity and its complication.
Keywords: obesity; raw faba bean; germination; cooking; rats